Developing the role of the tissue viability nurse – a workforce perspective - Tanya Haines (British Journal of Community Nursing, 2026)
This article explores existing literature for clarity and insights regarding the tissue viability nurse role. This review was prompted by the author's curiosity and questions about clinical development pathways as there is ambiguity about the role and varying opinions about the clinical activities that should be undertaken by tissue viability nurses. The article reviews the role, value and impact of tissue viability nurses on patient outcomes, as well as on national service provision. The review further discusses some of the limitations and issues the specialism faces and potential new opportunities for service development as the NHS fit for the future plan is implemented.